Effects of biological admixtures on hydration and mechanical properties of Portland cement paste. (28th February 2020) - Kim, Hayeon; Son, H.M.; Park, Solmoi; Lee, H.K.
Highlights: Properties of cement were more affected by components of nutrients than by the microbial metabolism. The calcium source could improve the mechanical properties by accelerating the hydration rate. Vegetative cells of ureolytic bacterium can reduce porosity by bio-mediated calcification. Abstract: The present study investigated the effects of biological admixtures on hydration kinetics and mechanical properties of Portland cement paste. The biological admixtures consisted of nutrient, urea, calcium lactate, and ureolytic bacterium, and were added to the cement slurry during the mixing process in a solution form. The ureolytic bacterium was newly isolated in river sediment, and was incorporated in a vegetative cell state. Five types of specimens with varying components of the biological admixtures were water-cured for 28 days. To evaluate the hydration kinetics and mechanical properties of Portland cement paste with biological admixtures, isothermal calorimetry, thermogravimetry, mercury intrusion porosimetry, and a compressive strength test were conducted. The obtained results showed that the mechanical properties were improved due to the porosity reduced by CaCO3 precipitation metabolism of ureolytic bacterium. Further, the hydration was delayed by biological admixtures, and was more affected by components of nutrients than by microbial metabolism.